Projeto e implementação em FPGA de um processador com conjunto de instrução reconfigurável utilizando VHDL - Casillo, Leonardo Augusto (2006)
The Reconﬁgurable Computing is an intermediate solution at the resolution of complex problems, making possible to combine the speed of the hardware with the ﬂexibility of the software. An reconﬁgurable architecture possess some goals, among these the increase of performance. The use of reconﬁgurable architectures to increase the performance of systems is a well known technology, specially because of the possibility of implementing certain slow algorithms in the current processors directly in hardware. Amongst the various segments that use reconﬁgurable architectures the reconﬁgurable processors deserve a special mention. These processors combine the functions of a microprocessor with a reconﬁgurable logic and can be adapted after the development process. Reconﬁgurable Instruction Set Processors (RISP) are a subgroup of the reconﬁgurable processors, that have as goal the reconﬁguration of the instruction set of the processor, involving issues such formats, operands and operations of the instructions. This work possess as main objective the development of a RISP processor, combining the techniques of conﬁguration of the set of executed instructions of the processor during the development, and reconﬁguration of itself in execution time. The project and implementation in VHDL of this RISP processor has as intention to prove the applicability and the efﬁciency of two concepts: to use more than one set of ﬁxed instructions, with only one set active in a given time, and the possibility to create and combine new instructions, in a way that the processor pass to recognize and use them in real time as if these existed in the ﬁxed set of instruction. The creation and combination of instructions is made through a reconﬁguration unit, incorporated to the processor. This unit allows the user to send custom instructions to the processor, so that later he can use them as if they were ﬁxed instructions of the processor. In this work can also be found simulations of applications involving ﬁxed and custom instructions and results of the comparisons between these applications in relation to the consumption of power and the time of execution, which conﬁrm the attainment of the goals for which the processor was developed